Freire's ontological perspective on the awakening of the student's conscience through teaching - Loayza Maturrano, Edward Faustino (2022)
On the centenary of Paulo Freire’s birth, the interpretation of oppression and liberation in Pedagogy of the Oppressed still has a human value across cultures, space and time, inspiring educators to rethink teaching, as the subjective consciousness of students is obscured from an ontological perspective. This theoretical study analyzes from an ontological perspective the discovery of a new student and a new teacher. A student with the exercise of subjective awareness in teaching and a teacher with greater efficiency overcoming the barriers of inequality through the pedagogy of dialogue and the cultivation of the critical conscience of the student with the purpose of dignifying the student through his agent role in teaching activities that is currently denied. In addition, some discussions are established, practical solutions to achieve a change in education and teaching.